Degradation Analysis on Manufacture of Cement-bonded Particleboard Using Supercritical CO2 - Rohny Setiawan Maail (Wood Research Journal, 2013)
This study analyzed the degradation process on manufacture of cement-bonded particleboard (CBP) using supercritical CO2. CBP with a target density of 1.2 g/cm3 was manufactured at a cement / wood particle / water weight ratio of 2.5:1.0:1.25. As references, neat cement board (NC) was manufactured at a cement / water weight ratio of 2.5:1.25, and Ca(OH)2 board was manufactured at a Ca(OH)2 / wood particle / water weight ratio of 3.0:1.0:1.5. Hand-formed mat of 230 x 230 mm was cold-pressed to a targeted thickness of 12 mm and kept in an oven set at 60ºC for 24 h. Four specimens of 50 x 210 mm prepared from these boards were then used for curing treatment. The three curing treatments were (1) supercritical CO2 treatments, 10 min to 10 days; (2) conventional curing treatment for 28 days (Conventional); and (3) neither curing nor supercritical CO2 treatment as the control. The chemical changes and the mineralogical composition of the curing and the degradation processes of the CBP were examined using X-ray diffractometry (XRD), thermal gravimetry (TGA-DTG), and scanning electron microscopy (SEM) observation. Significant correlations were found between the supercritical CO2 treatment and mechanical properties during both the curing and degradation processes. Internal bond (IB) strength, modulus of rupture (MOR), and modulus of elasticity (MOE) values of CBP achieved their maximums by supercritical CO2 treatment in 30 min. These conditions indicated that supercritical CO2 treatment accelerates the curing process rapidly and enhances the mechanical properties of the CBP.  However, these values decreased in the treatments from 60 min to 10 days and had a negative effect on board performance, indicating that supercritical CO2 treatment over a longer time span leads to the degradation of the CBP. Furthermore, X-ray diffractometry (XRD), thermal gravimetry (TG-DTG), and scanning electron microscopy (SEM) observation clarified that the mechanisms of the degradation are directly affected by the mineralogical composition of the system, in particular by the calcium carbonate content as caused by carbonation.